PROTECTION OF HOUSEHOLD APPLIANCES INDUCTION MOTORS AGAINST OVERCURRENT TAKING INTO ACCOUNT NONLINEAR DISTORTION OF PHASE CURRENT - Sereda, O. G.; Varshamova, I. S. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2015)
Purpose. Theoretical justification and engineering of induction motors heat protection method from overload currents taking into account nonlinear distortion of the phase current and implementation as a microprocessor device functioning algorithm. Methodology. To solve the problem used the theory of the representing complex harmonic oscillations analog signals expansion into the oscillation spectrum forming elementary harmonic components in order to compare their properties by applying the theory of discrete signals and systems, as well as methods of spectral analysis and discrete signals filtering. The harmonic analysis versatility is that any periodic signal may be synthesized from harmonic oscillation of certain amplitude, frequency and initial phase. A mathematical model for determining the phase current harmonic content of power supply networks with isolated neutral and non-linear loads types and, as a consequence, the distortion of sinusoidal phase current change is developed by multiplying the analog current in time dependency on the grate delta-function with different sampling intervals, in which the use of simple and widely used in relay protection units, in particular electronic overcurrent relays, mathematical operations of integration squares instantaneous current allows the most in harmony with the mathematical tools to build other network protection types. Findings. The necessity to increase the sensitivity of the induction motors heat protection from overload currents taking into account nonlinear distortion of the phase currents is proved. By nonlinear distortion harmonic analysis of the phase currents the motor protection reliability increasing provided by taking into account the higher harmonic components of the phase currents, which causes to additional losses and heating of the stator winding. It uses the simplest and widely used in protective relaying mathematical apparatus determining of most significant higher harmonics currents RMS. Originality. A possibility of extending the implemented protection list of electronic overcurrent relays based on the digital processing of signals from the current sensors is theoretical research by the harmonious analysis of phase current spectrum with the nonlinear distortions presence. A new technical solution is proposed that allows in online sliding monitoring mode to form response time of electronic overcurrent relays for reliable protection of induction motors from overload currents taking into account nonlinear distortion of the phase current. Practical value. A microprocessor protection functioning algorithm of induction motors is designed against impermissible heating coils with overload currents taking into account nonlinear distortion of the phase current.